Towards an Agentive Understanding of Political Silence (KULT_online, 2019)
The edited volume Political Silence: Meanings, Functions and Ambiguity (2018) provides a fresh perspective on matters of voice and representation within the realm of International Relations. The publication’s focus – silence – is commonly understood as the opposite of voice, and is therefore often interpreted negatively, as a lack of agency, or as the result of exclusion or oppression. Here, a central aim is to create a critical distance to this reductive understanding of silence, and instead to interpret it positively, emancipating it from its subsidiary position vis-à-vis the spoken word, as its own modality of political agency. Although not all individual contributions achieve this ambitious aim to the same extent, the volume generally presents a convincing argumentative direction in which silence is conceptualized not as exclusion from, but rather as constitutive of, political subjectivity. By approaching the concept from different disciplinary groundings, and working from a variety of historical and contemporary case studies, the contributors invite their readers to consider silence as a force of political change.